Fast degrading bioresorbable arterial vascular graft with high cellular infiltration inhibits calcification of the graft - Sugiura, Tadahisa (J Vasc Surg, 2016)
OBJECTIVE: Bioresorbable vascular grafts are biologically active grafts which are entirely reconstituted by host-derived cells through an inflammation-mediated degradation process. Calcification is a detrimental condition that can severely impact graft performance. Therefore, prevention of calcification is of great importance to the success of bioresorbable arterial vascular grafts. The objective of this study is to test whether fast degrading bioresorbable arterial grafts with high cellular infiltration will inhibit calcification of grafts. METHODS: We created two versions of bioresorbable arterial vascular grafts: 1) Slow Degrading (SD) grafts and 2) Fast Degrading (FD) grafts. Both grafts had the same inner layer composed of a 50:50 poly (l-lactic-co-ε-caprolactone) copolymer (PLCL) scaffold. However, the outer layer of SD grafts was composed of poly (l-lactic acid) (PLA) nano-fiber whereas the outer layer of FD grafts was composed of a combination of PLA and polyglycolic acid (PGA) nano-fiber. Both grafts were implanted in 8–10 week old female mice (n = 15 in the SD group, n = 10 in the FD group) as infra-renal aortic interposition conduits. Animals were followed for 8 weeks. RESULTS: Von Kossa staining showed calcification in 7 out of 12 grafts in the SD group, but zero in the FD group (P<.01, chi-square test). The cell number in the outer layer of FD grafts was significantly higher than SD grafts (SD: 0.87 ± 0.65 × 10(3)/mm(2) vs. FD: 2.65 ± 1.91 × 10(3)/mm(2), P=.02). CONCLUSIONS: The fast degrading bioresorbable arterial vascular graft with high cellular infiltration into the scaffold inhibited calcification of grafts.